Establishing the dependence of fatty acids content and lipid quality on maturity term of the alpine and yogurt hard goat cheeses - Davydovych, Viktor; Shevchenko, Larysa; Slobodyanyuk, Natalia; Furman, Svitlana; Bandura, Valentyna; Lebedenko, Tetiana; Sydorenko, Olena; Kovalenko, Nataliia; Nesterenko, Natalia (Eastern-European Journal of Enterprise Technologies, 2026)
The Alpine and Yogurt craft hard cheeses made from unpasteurized goat milk are studied in this paper. The task under consideration is to define the authenticity criteria for the Alpine and Yogurt craft goat cheeses made from unpasteurized milk during maturity process. Consumers' orientation towards healthy eating leads to an increase in the supply of craft cheeses made from unpasteurized goat milk on the market, which involves assessing their quality, safety, and establishing authenticity criteria. Such indicators include the fatty acid composition and quality of milk fat lipids. The fatty acid composition of the cheeses has been analyzed using gas chromatography. The lipid structure of both cheeses contained 15 fatty acids (11 saturated and 4 unsaturated). The share of saturated fatty acids increased by 4.04–4.44% at the 18th month of maturity of the Yogurt cheese and at the 6th month of maturity of the Alpine cheese. During the maturity process, the proportion of polyunsaturated fatty acids in the Alpine cheese increased by 1.60–2.07%; in the Yogurt cheese by 1.24–2.35%. In both cheeses, the basis of ω-3 and ω-6 polyunsaturated fatty acids was linolenic and linoleic; their ratio ranged from 1:4.26 to 1:2.31. The ripened Alpine and Yogurt cheeses were characterized by the highest indices of thrombogenicity and atherogenicity, in contrast to old-ripened cheeses, in which these indices decreased against the background of an increase in the indices of hypocholesterolemic/hypercholesterolemic acids and healthy fat. The delta nine desaturase index (C14) during maturity period of the Alpine cheese decreased by 0.010–0.011; in the Yogurt cheese, on the contrary, it increased by 0.054–0.026 units. The fatty acid composition of goat craft hard cheeses could be a justification for devising criteria for their authenticity and nutritional value